Anthocyanins - M. Monica Giusti (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
This book contains 20 articles published in Molecules that concern the color quality of food and wine, anthocyanin biosynthesis and regulation, anthocyanin composition and the biological properties of anthocyanin pigments.